Telomere length and urinary 8-hydroxy-2'-deoxyguanosine and essential trace element concentrations in female Japanese university students. Issue 12 (15th October 2021) - Mizuno, Yuki; Konishi, Shoko; Imai, Hideki; Fujimori, Eiji; Kojima, Nobuhiko; Kajiwara, Chiaki; Yoshinaga, Jun
Abstract: Telomere length is thought to be a biomarker of biological aging. This study examined whether telomere length was associated with urinary concentrations of 8-hydroxy-2'-deoxyguanosine (8-OHdG), a biomarker of oxidative stress, and antioxidative trace elements in 73 female Japanese university students (age: 19.2 ± 0.7 years). We quantified 8-OHdG and selenium in urine by liquid chromatography–mass spectrometry and inductively coupled plasma-mass spectrometry, respectively. Telomere length and urinary concentrations of other essential trace elements (molybdenum, cobalt, and chromium) that were previously measured in the same study participants, were used in this study. We used multiple linear regression analysis to examine the associations of telomere length with urinary 8-OHdG and essential trace element concentrations (covariates: urinary cotinine concentration, age, BMI, and drinking status). The geometric means (geometric standard deviation) of 8-OHdG and selenium were 3.4 (1.5) and 31 (1.3) µg/g creatinine, respectively. Telomere length was not associated with urinary 8-OHdG concentration, but was negatively associated with urinary selenium concentration. In conclusion, telomere length was not associated with urinary 8-OHdG concentration in the young women in this study. Longitudinal studies should be conducted to clarify the association between telomere shortening rate and oxidative stress level.